ӘЖИНИЯЗ ҚОСЫБАЙ УЛЫ ПОЭЗИЯСЫНЫҢ ҮЙРЕНИЛИЎ ДӘРЕЖЕСИ - Ажиниязова, А.П. (SCIENCE and SOCIETY, 2025)
In the article, the level of study of the sharia of the son of Ajiniyaz Kusibay, a representative of the classic literature of Karakalpak literature of the 19th century, was studied. After seeing the scientific researches of literary scholars, we expressed our relations with them.